2018
DOI: 10.1007/s00360-018-1174-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of desert pupfish at ecologically relevant temperatures suggests a significant role for anaerobic metabolism

Abstract: Oxygen consumption is oftentimes used as a proxy for metabolic rate. However, pupfish acclimated to ecologically relevant temperatures may employ extended periods of anaerobism despite the availability of oxygen-a process we called paradoxical anaerobism. In this study, we evaluated data from pupfish exhibiting stable oxygen consumption. Routine oxygen consumption ([Formula: see text]) of a refuge population derived from Cyprinodon spp. acclimated to 28 and 33 °C was evaluated at the ecologically relevant assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…While this phenotype is frequently manifested by oxygen consumption that is more variable and lower than what may be otherwise expected, we believe a positive feedback mechanism resulting in more and more closure of the VDACs results in the paradoxical anaerobism characterized by negligible oxygen consumption. Consistent with this model are data from 33 °C-acclimated pupfish demonstrating a much higher frequency of a state of variable oxygen consumption (~20% of 33 °C-acclimated pupfish assayed for 2 h as compared to <4% of 28 °C-acclimated pupfish), lower than expected oxygen consumption, and lower aerobic scope (maximum oxygen consumption • rVO 2 -1 ) [2,3]. In other words, both 28-and 33°C…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…While this phenotype is frequently manifested by oxygen consumption that is more variable and lower than what may be otherwise expected, we believe a positive feedback mechanism resulting in more and more closure of the VDACs results in the paradoxical anaerobism characterized by negligible oxygen consumption. Consistent with this model are data from 33 °C-acclimated pupfish demonstrating a much higher frequency of a state of variable oxygen consumption (~20% of 33 °C-acclimated pupfish assayed for 2 h as compared to <4% of 28 °C-acclimated pupfish), lower than expected oxygen consumption, and lower aerobic scope (maximum oxygen consumption • rVO 2 -1 ) [2,3]. In other words, both 28-and 33°C…”
Section: Discussionsupporting
confidence: 58%
“…The Mojave Desert in the Southwestern United States is a home to isolated systems of springs that are geothermally or ambiently heated to 28 to 33 °C and are inhabited by pupfish in the genus Cyprinodon [1]. Previously, we demonstrated that two lineages of pupfish reared at 33 °C frequently entered a state of paradoxical anaerobism [2,3]. For periods of as much as 149 minutes, these pupfish consumed negligible oxygen despite its availability.…”
Section: Introductionmentioning
confidence: 99%
“…While this phenotype is frequently manifested by oxygen consumption that is more variable and lower than what may be otherwise expected, we believe a positive feedback mechanism resulting in more and more closure of the VDACs results in the paradoxical anaerobism characterized by negligible oxygen consumption. Consistent with this model are data from 33 °C-acclimated pupfish demonstrating a much higher frequency of a state of variable oxygen consumption (~ 20% of 33 °C-acclimated pupfish assayed for 2 h as compared to < 4% of 28 °C-acclimated pupfish), lower than expected oxygen consumption, and lower aerobic scope (maximum oxygen consumption • rVO 2 − 1 ) [ 2 , 3 ]. In other words, both 28- and 33 °C-acclimated pupfish are likely using a mosaic of both paradoxical anaerobism and oxygen consumption.…”
Section: Discussionmentioning
confidence: 61%
“…Routine rates of oxygen consumption (rVO 2 ) were measured in fish showing minimal activity using flow-through respirometry (Fig. S1 ) [ 2 , 3 ]. Briefly, four fish at a time were placed individually in glass metabolic chambers (60 mL volume) that were connected to flow cells with Clark-type oxygen electrodes (Strathkelvin, Scotland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation